At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's work through the problem step-by-step.
We are given the following functions:
[tex]\[ f(x) = 3x + p \][/tex]
[tex]\[ g(x) = px + 4 \][/tex]
We also know that:
[tex]\[ f(g(x)) = 6x + q \][/tex]
First, let’s determine [tex]\( f(g(x)) \)[/tex].
1. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
First, we find [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = px + 4 \][/tex]
Now substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(px + 4) \][/tex]
2. Evaluate [tex]\( f(px + 4) \)[/tex]:
Using the expression for [tex]\( f(x) \)[/tex]:
[tex]\[ f(px + 4) = 3(px + 4) + p \][/tex]
3. Expand and simplify:
[tex]\[ f(px + 4) = 3(px) + 3(4) + p \][/tex]
[tex]\[ f(px + 4) = 3px + 12 + p \][/tex]
4. Set this equal to the given expression for [tex]\( f(g(x)) \)[/tex]:
We know from the problem statement:
[tex]\[ f(g(x)) = 6x + q \][/tex]
Therefore,
[tex]\[ 3px + 12 + p = 6x + q \][/tex]
5. Equate the coefficients of [tex]\( x \)[/tex] and the constant terms:
By comparing the coefficients of [tex]\( x \)[/tex] on both sides of the equation,
[tex]\[ 3p = 6 \][/tex]
Solving for [tex]\( p \)[/tex]:
[tex]\[ p = \frac{6}{3} \][/tex]
[tex]\[ p = 2 \][/tex]
6. Substitute [tex]\( p = 2 \)[/tex] into the constant term equation:
Now we substitute back into the equation for the constants,
[tex]\[ 12 + p = q \][/tex]
Substitute [tex]\( p = 2 \)[/tex]:
[tex]\[ 12 + 2 = q \][/tex]
[tex]\[ q = 14 \][/tex]
Therefore, the values of the constants are:
[tex]\[ p = 2 \][/tex]
[tex]\[ q = 14 \][/tex]
This completes the step-by-step solution to the problem.
We are given the following functions:
[tex]\[ f(x) = 3x + p \][/tex]
[tex]\[ g(x) = px + 4 \][/tex]
We also know that:
[tex]\[ f(g(x)) = 6x + q \][/tex]
First, let’s determine [tex]\( f(g(x)) \)[/tex].
1. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
First, we find [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = px + 4 \][/tex]
Now substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(px + 4) \][/tex]
2. Evaluate [tex]\( f(px + 4) \)[/tex]:
Using the expression for [tex]\( f(x) \)[/tex]:
[tex]\[ f(px + 4) = 3(px + 4) + p \][/tex]
3. Expand and simplify:
[tex]\[ f(px + 4) = 3(px) + 3(4) + p \][/tex]
[tex]\[ f(px + 4) = 3px + 12 + p \][/tex]
4. Set this equal to the given expression for [tex]\( f(g(x)) \)[/tex]:
We know from the problem statement:
[tex]\[ f(g(x)) = 6x + q \][/tex]
Therefore,
[tex]\[ 3px + 12 + p = 6x + q \][/tex]
5. Equate the coefficients of [tex]\( x \)[/tex] and the constant terms:
By comparing the coefficients of [tex]\( x \)[/tex] on both sides of the equation,
[tex]\[ 3p = 6 \][/tex]
Solving for [tex]\( p \)[/tex]:
[tex]\[ p = \frac{6}{3} \][/tex]
[tex]\[ p = 2 \][/tex]
6. Substitute [tex]\( p = 2 \)[/tex] into the constant term equation:
Now we substitute back into the equation for the constants,
[tex]\[ 12 + p = q \][/tex]
Substitute [tex]\( p = 2 \)[/tex]:
[tex]\[ 12 + 2 = q \][/tex]
[tex]\[ q = 14 \][/tex]
Therefore, the values of the constants are:
[tex]\[ p = 2 \][/tex]
[tex]\[ q = 14 \][/tex]
This completes the step-by-step solution to the problem.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.